Long-term effectiveness of two models of brief psychotherapy for depression: A three-year follow-up randomized clinical trial. (April 2020) - dos Santos, Érico Nobre; Molina, Mariane Lopez; Mondin, Thaise; Cardoso, Taiane de Azevedo; Silva, Ricardo; Souza, Luciano; Jansen, Karen
Highlights: This is the first long-term follow-up (three years) of psychotherapy for depression only to assess global functioning. It is the second ever long-term follow-up study for depression treatment to evaluate global functioning. It was found a maintenance of the therapeutic response on depressive symptoms after three years and that functional capacity long-term maintenance depends not only on the intervention. Abstract: Major depressive disorder (MDD) is a disease that severely impairs psychosocial functioning and decreases the subject's quality of life. Patients who received psychotherapy have a better long-term therapeutic response than those who have only been treated with antidepressants or have not been treated. There are few studies in the literature that follow the outcomes of psychotherapeutic treatments for depression for more than two years. The aim of this study is to compare the therapeutic response of two models of brief psychotherapy for MDD treatment (Cognitive Behavioral Therapy and Short-term Psychodynamic Psychotherapy) with naturalistic controls who received treatment as usual in a three-year follow-up. This is a sample of 75 outpatients, mostly women (82.7%), with a median age of 33 (27–44). The interventions took place in 50-minute sessions once a week for 14 to 16 weeks. Outcomes were assessed at baseline and three years after the intervention. Regarding depressive symptoms, the therapeutic response was maintained three years after the conclusion of the brief models of psychotherapy. Functional capacity long-term maintenance depended not only on the intervention but also on the education level, the work situation and the severity of depressive symptoms at the beginning of the treatment.